Novel mesoporous anionic substituted hydroxyapatite particles for multipurpose applications. Issue 5 (1st March 2022) - Aggarwal, Anoop; Singh, Ravinder Pal; Danewalia, Satwinder Singh; Saggu, Harminder Singh
Abstract: The super-structured nanodimensional apatitic particles have been limited explored for therapeutic applications. Furthermore, ion substituted super-structured nanodimensional apatitic particles have been rarely attempted, which motivated the present investigation. In the present work, F − and Cl − substituted hydroxyapatite (HAP) prepared via a facile and economical one-pot hydrothermal route were characterized for their structural, morphological and bioactive properties. The F − and Cl − anions (1 wt%) were individually substituted in hierarchically assembled nanostructured apatitic (HANA) particles and produced fluorine substituted Hydroxyapatite (FHAP) and chlorine substituted Hydroxyapatite (ClHAP) HANA particles, respectively. Besides comprehensive characterization, particles were systematically tested for their in-vitro ionic dissolution and drug-carrying abilities. Both FHAP and ClHAP nanoparticles exhibited monolithic apatitic structure, novel spherical morphology having substituted elements, mesoporous large surface area, and pore-volume with high thermal stability. Furthermore, both particles exhibited superior in-vitro bioactivity ability. Besides it, both FHAP and ClHAP nanoparticles exhibited superior drug loading and sustained drug release characteristics. Thus, this study presented the potentials of novel particle shapes with superior bioactivity and drug-carrying abilities, making them suitable for multipurpose therapeutic applications, including tissue regeneration and drug-carrying agents.